STUDIES OF PPLO INFECTION : I. THE PRODUCTION OF CEREBRAL POLYARTERITIS BY MYCOPLASMA GALLISEPTICUM IN TURKEYS; THE NEUROTOXIC PROPERTY OF THE MYCOPLASMA - Thomas, Lewis (The Rockefeller University Press, 1966)
Turkey poults injected intravenously with suspensions of Mycoplasma gallisepticum develop a fatal neurologic disease associated with polyarteritis affecting almost exclusively the cerebral arteries. The incubation period depends on the dose of organisms. With high doses (10(10) to 10(11) mycoplasmas) the birds become ill and die within a few hours; with lower doses (10(6) to 10(8)) neurologic manifestations appear after 7 days. The rapid onset of neurologic signs after high doses indicates the presence of a toxin in the mycoplasma, but efforts to extract toxin from disrupted organisms or to demonstrate its presence in culture fluid free of mycoplasmas have been unsuccessful. The toxin appears to be associated only with living mycoplasmas. The toxic component of M. gallisepticum is inactivated by heating the organisms at 50°C, disruption by repeated cycles of freezing and thawing, and exposure to specific antibody. Treatment of turkeys with gold thiomalate furnishes partial protection against the toxic effects of large doses of mycoplasmas, and protection against the development of cerebral arteritis. Treatment with tetracycline protects completely against both toxicity and arteritis, and, when delayed, restores diseased birds to a healthy state. Cortisone, methotrexate and 6-mercaptopurine have no effect on the course or outcome of the disease. Intracerebral injections of M. gallisepticum are less toxic and lethal than when the same dose was given by vein, indicating that the organism exerts its damaging action on blood vessels by way of the blood stream. The arterial lesions resemble those of serum sickness, except for their distribution, and are associated with glomerular inflammatory lesions. However, for various reasons discussed, it is considered more likely that they result from a direct toxic action of living mycoplasmas on the vessels concerned than from an immunologic mechanism.